Diseño de una taxonomía en XBRL para el reporte de estado de flujo de efectivo bajo los parámetros establecidos en la norma internacional de contabilidad No 7 (2012)
XBRL is emerging as a powerful international standard for efficient and effective scanning of any type of report issued by organizations (not just financial reports, as many would come to think). The XBRL standard organizational reports gives an "intelligent structure" that allows the stakeholder to use this information to avoid the problems commonly found in data manipulation, such as loss of valuable information, reprocessing of information, irrelevant information or unimportant to the stakeholder, and so on.